Unfinished Business: Evolving Capitalism in the World$1 (Bs Largest Democracys - Reviewed by Mallikarjun Gudadinni and Nabendu Paul (Vikalpa: The Journal for Decision Makers)
Vijayaraghavan, Nandini. Unfinished Business: Evolving Capitalism in the World$1 (Bs Largest Democracy: Penguin Bussiness, 2023, 386p. $1,495s